Pengembangan Instrumen Tes Kemampuan Berpikir Kreatif Berbasis Pendekatan Konflik Kognitif - Rangga Alif Faresta; Walid Anggara; Tegar Agusfian Mandiri; Adi Septiawan (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2020)
The ability to think creatively is part of the affective domain that also determines the success of learning. The researcher intends to conduct developmental research to produce a viable creative thinking tool. So that it can be used as a tool to assess students' creative thinking ability. This research is a development research or Research and Development (R&D) with the 4D model, namely Define, Design, Develop and Disseminate. In this study, it was only performed up to the development phase, namely expert validation and practitioner validation. The tools developed were descriptive questions. The sample used were class X high school students. Based on the expert validator's rating, the demand for creative thinking averaged 3.25 in all aspects with a very good category and a content validation value of 0.71 in the valid category. Meanwhile, the practitioner validator rating achieved the feasibility of the mean value of all aspects of 3.71 with the very good category and the content validation of 0.89 with the valid category. Thus, it can be concluded that the creative thinking assessment tool is suitable to be used to measure students' creative thinking level